Desain Dan Optimasi Proses Pirolisis Waste Oil Menggunakan Pendekatan RSM - Sukoco, Dody (Jurnal Inovasi Teknologi Terapan, 2023)
The management of abundant oil waste in companies that are spread over tin mining operational locations is still not optimal. The waste oil comes from engine oil and hydraulic oil. With proper management, waste oil will become useful and have added value. This waste can be processed into HSD (High Speed ​​Diesel) fuel, so the company will get profit. The processing method used in waste treatment is the pyrolysis process. In this study, a pyrolysis tool was designed and built, and a test was carried out to obtain optimal parameters for the resulting fuel product using the Response Surface Methodology (RSM) method. The tests were carried out using activated Zeolite powder catalyst and 1000 ml of oil in each test. The indicators and parameters observed are the Quantity HSD and the percentage of Zeolite. The results of the optimization of the research process with the optimum formulation, namely setting temperature 285 oC, catalyst 109.8 gr, product yield 898.1 ml. Where as in the use of Raw Material Hydraulic Oil, the optimum formulation is a temperature of 325.8 oC, 118.6 gr catalyst, and a product yield of 920 ml with a duration of 60 minutes.